Ответ:
Пошаговое объяснение:
74*147 - 73 73*147+(147-73 ) 73*147+74
--------------- = ------------------------ = --------------------- = 1
73*147+74 73*147+74 73*147+74
Ответ:1)10805 2)10805
10878-73=10805
73*147=10731
10731+74=10805
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
74*147 - 73 73*147+(147-73 ) 73*147+74
--------------- = ------------------------ = --------------------- = 1
73*147+74 73*147+74 73*147+74
Ответ:1)10805 2)10805
Пошаговое объяснение:
10878-73=10805
73*147=10731
10731+74=10805